(untitled) (Research, Society and Development, 2022)
Objective: Identifying and synthesizing the scientific evidence of cancer patient safety in teletherapy treatment. Methodology: This is a scoping review according to Joanna Briggs Institute and PRISMA-ScR. Research conducted from October 2021 to January 2022 in the databases National Library of Medicine and National Institutes of Health, Cummulative Index to Nursing and Allied Health Literature, Web of Science, SCOPUS, Latin American and Caribbean Literature in Health Sciences, Embase, Cochrane Library and eight catalogs of theses and dissertations without application of time limit. Results: Sixty-seven studies were selected for this review, 85.08% are descriptive and the majority (53.73%) were conducted in the United States of America, in general the studies were produced by multidisciplinary health groups. The evidence found recommends the use of the following measures to prevent and reduce the occurrence of incidents by teletherapy treatment: implement risk management programs and processes; promote safe workflow; use voluntary incident reporting and incident learning systems and promote the patient safety culture. Final notes: Patient safety under teletherapy treatment occurs when there is the management of risks and processes and the promotion of safety culture based on evidence and practiced through institutional and multidisciplinary efforts.